If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-4=8x(x-1)
We move all terms to the left:
3x-4-(8x(x-1))=0
We calculate terms in parentheses: -(8x(x-1)), so:We get rid of parentheses
8x(x-1)
We multiply parentheses
8x^2-8x
Back to the equation:
-(8x^2-8x)
-8x^2+3x+8x-4=0
We add all the numbers together, and all the variables
-8x^2+11x-4=0
a = -8; b = 11; c = -4;
Δ = b2-4ac
Δ = 112-4·(-8)·(-4)
Δ = -7
Delta is less than zero, so there is no solution for the equation
| 17-x+2x/3=4/3 | | 2g+5=20-g | | -9b(3b+1)+(28b-7)=0 | | 6x-30=8x-50 | | (9+x)(3x+4)=0 | | 9(13x)−x213x=0 | | 44/x=20/180 | | 8x+4x+4+7=9x+3+2x | | 40x-5=30 | | 14-x=84 | | x-14=84 | | x3+7x2+2=0 | | 3/c=9/27 | | 3(x-9)=99/11 | | 3u-14u+8=0 | | 7a-17=5a-14 | | 8•(x+3)=14 | | M/18=15/m | | 4x+2(30-x)=86 | | x÷0.8=15 | | x^2+x^2+50x=600 | | r^2+r^2+50r=600 | | x/6x-36-8=1/x-6 | | 4(u+1)=-20 | | 4(u=1)=-20 | | -30/r=5 | | 3(6-k)=69 | | 6x+x=9x+x | | 3x^2=5.5 | | 3x^2=5/5 | | 9x+x=45 | | -2x/5+3=-5 |